The top 100 most-cited articles on exercise therapy for sarcopenia: A bibliometric analysis - Guo, Zhao-jing; Xie, Wen-qing; Cai, Zi-jun; Zhang, Yue-yao; Ding, Yi-lan; Naranmandakh, Shinen; Li, Yu-sheng; Xiao, Wen-feng (Frontiers in Medicine, 2022)
Objective: Vast quantities of literature regarding the applications of exercise therapy for sarcopenia has been published. The main objective of this study is to determine the top 100 most-cited articles and analyze their bibliometric characteristics. Design: This study reports a bibliometric analysis via a systematic search of the academic literature regarding the applications of exercise therapy for sarcopenia. Methods: All databases in the Web of Science were searched with the following strategy: term search (TS) = (exercise* OR training OR "physical activit*") AND TS=(sarcopenia) on 25 February 2022. The results were presented in descending order by their total citations. List of the top 100 articles was finally determined by negotiation of two independent researchers. Results: The top 100 articles were published between 1993 and 2020. More than half of the articles (n=54) were published during the decade 2006-2015. Total citations of the top 100 articles ranged from 155 to 1131 with a median of 211.5. The average of annual citations was constantly increasing with year (P<0.05). The most studied exercise therapy is strength/resistance training, with about 71% articles had discussed about it. The top 100 articles were from 54 different journals, Journal of Applied Physiology was the journal contributed the most articles (n=8). A total of 75 different first corresponding authors from 15 countries made contributions to the top 100 list. Luc J.C. van Loon from the Maastricht University in Netherlands published the most articles (n=5) as the first corresponding author. Most articles (87%) were from North America (58%) and Europe (29%), while USA as a country contributed over half of the articles (51%). Conclusions: Our study determined the top 100 most-cited articles on exercise therapy for sarcopenia and analyzed the bibliometric characteristics of them, which may provide a recommended list for researchers in this field and pave the way for further research.